AT ITALESÆTTE VOLDEN: Hverdagens og fortidens overgreb blandt indfødte i Chile - Kristensen, Dorthe Brogård (Tidsskriftet Antropologi, 2002)
By focusing on narratives and life-stories among Mapuche Indians in the South of Chile the article discusses how different types of expressions and social organizations give actors a way of articulating and managing experiences of social and structural violence. The article also describes